Effects of activated carbon and four different biochars on fermentation in the artificial rumen (RUSITEC) - Weinberg, Alexander; Witte, Franziska; Schubert, Dana Carina; Rohn, Karl; Hoeltershinken, Martin; Hancock, Victoria Eva; Sitzmann, Werner; Terjung, Nino; Visscher, Christian (Frontiers in Animal Science, 2025)
Anthropogenic climate change is primarily caused by CO2 and CH4 emissions, with a significant portion originating from agriculture and livestock. Reducing methane emissions in ruminant husbandry has been a longstanding goal. Therefore, in this study, we aimed to influence the fermentation processes in the artificial rumen model (rumen simulation technique, RUSITEC) using five different carbons—one activated carbon (AC) and four biochars (BCs)—and one control without supplement. The carbons were included at 2% of dry matter (DM) of the basal diet, which corresponded to 0.3 g DM of the assigned additive. The treatments were conducted on 12 fermenters with two replications (n = 4/treatment) in a randomized block design. The experimental period consisted of a 7-day adaptation phase and an 8-day data and sample collection phase. Parameters included gas volume, gas composition, disappearance rates, volatile fatty acid (VFA) production, and nutrient digestion. Except for biochar (BC) 3, carbons showed no impact on gas parameters, while BC 3 decreased CO2 production (p = 0.0453), gas volume (p = 0.0255), and the ratio of CO2 (p = 0.0304), CH4 (p = 0.0304), and gas volume (p = 0.0304) to disappeared organic matter (dOM). BC 3 also showed a tendency to decrease in methane production (p = 0.0878). The effects on produced VFA were only found for BC 3, which reduced the daily production of total VFA (p = 0.0226), acetic acid (p = 0.0248), propionic acid (p = 0.0166), i-butyric acid (p = 0.0366), and the ratio of VFA to dry matter loss (p = 0.0172) and to dOM (p = 0.0304), while pH (p = 0.0309) was higher compared to the control. Only BC 3 had decreasing effects on disappearance rates (p = 0.0304). Although BC 3 reduces greenhouse gas emissions, it does so at the expense of fermentation, as indicated by its decreasing impact on digestion rate, VFA production, and the resulting increase in pH. In conclusion, biochar has the potential to affect rumen fermentation in vitro. However, general statements regarding the effects of biochars on fermentation cannot be derived from this experiment; each biochar source needs to be evaluated individually.